EVALUASI PROGRAM PRAKTIK LAPANGAN PERSEKOLAHAN DENGAN MENGGUNAKAN MODEL CSE-UCLA - Sidik, Firman; Rasyid, Muhammad Nur Akbar; Mania, Sitti (LP2M IAIN Sultan Amai Gorontalo, 2023)
This article aims to analyze and evaluate the School Field Practice program. This program evaluation research uses an evaluation model developed by Alkin, namely CSE-UCLA